Prevalence of erectile dysfunction in men over 40 years of age in Turkey: Results from the Turkish Society of Andrology Male Sexual Health Study Group - Cayan, Selahittin; Kendirci, Muammer; Yaman, Onder; Asci, Ramazan; Orhan, Irfan; Usta, Mustafa Faruk; Kadioglu, Ates (Aves, 2017)
Objective: Previous study conducted by the Turkish Society of Andrology in 1999 reported the prevalence of erectile dysfunction (ED) as 69.2% in men of >= 40 years of age, using a single-item non-validated question. This rate seemed to be higher compared to the studies reported worldwide. So, there was a need to carry out another epidemiological study by using validated questionnaires. Our aim was to investigate ED prevalence, severity, and its correlates in men aged >= 40 years using validated tools. Material and methods: This cross-sectional, observational, population-based field survey was carried out in randomly selected males of >= 40 years from 19 provinces of Turkey. All participant completed a survey included with socio-demographic and socio-economic characteristics, medical and sexual history, associated physical and medical comorbidities. Erectile function was assessed by the International Index of Erectile Function (IIEF) questionnaire based on a total score of 30. The prevalence of ED, its severity and correlates in men aged >= 40 years were determined for main outcome measures. Data sets were statistically compared and p<0.05 was considered as significant. Results: Median age of 2.760 males was 54.2 years. The median prevalence of ED was calculated as 33% among all males of >= 40 years of age. When subjects were stratified by age; median ED prevalence rates were 17% for 40-49 years, 35.5% for 50-59 years, 68.8% for 60-69 years, and 82.9% for >= 70 years. Among all ED men, 76.9% reported mild, 16.3% moderate, and 5.7% severe ED. At logistic regression analyses; age, diabetes, hypertension, atherosclerosis, dyslipidemia, lower urinary tract symptoms, educational status and monthly income were found to be independent risk factors for having ED. Conclusion: This population-based survey in Turkish men of >= 40 years of age reported the prevalence of ED as 33%. Besides, this study reported age as the main predictor for presence and severity of ED.
Türkiye’de 40 yaş üstü erkeklerde erektil disfonksiyon prevalansı: Türk Androloji Derneği Erkek Seksüel Sağlığı Çalışma Grubu sonuçları
Keywords: Comorbidities; diagnosis; ejaculatory disorders; epidemiology; erectile dysfunction; lower urinary tract symptoms; prevalence; risk factors; sexual dysfunction; vascular risk factors